2018
DOI: 10.1111/exd.13784
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulated SHARPIN may accelerate the development of atopic dermatitis through activating interleukin‐33/ST2 signalling

Abstract: SHARPIN is an important component of the linear ubiquitin chain assembly complex (LUBAC). Loss of function of SHARPIN results in eosinophilic inflammation in multiple organs including skin with Th -dominant cytokines and dysregulated development of lymphoid tissues in mice. The clinicopathological features are similar to atopic dermatitis (AD) in humans. In order to investigate the potential role of SHARPIN in the pathogenesis of AD, we performed genetic association study of the genotypes and haplotypes as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…HaCaT cells were maintained in DMEM (Gibco/ThermoFisher Scientific, Waltham, MA, USA) containing L‐glutamine and supplemented with 10% fetal bovine serum (Gibco/ThermoFisher Scientific). Transduction of cells with lentivirus was performed as described by Tang et al 7 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…HaCaT cells were maintained in DMEM (Gibco/ThermoFisher Scientific, Waltham, MA, USA) containing L‐glutamine and supplemented with 10% fetal bovine serum (Gibco/ThermoFisher Scientific). Transduction of cells with lentivirus was performed as described by Tang et al 7 …”
Section: Methodsmentioning
confidence: 99%
“…Total RNA isolation, reverse transcription (RT), reagent volumes and evaluation methods were performed as previously described by Tang et al 7 . Quantitative (q)PCR was performed (LightCycler 96 System; Roche Diagnostics GmbH, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lacy et al [10] found IgE levels in AD patients was associated with the haplotype TGAC in the IL10 promoter region. Tang et al [11] performed genetic association study of the genotypes and haplotypes and implicated that SHARPIN may be a novel participant in the pathogenesis of AD. Our study intends to define haplotypes from the previous genotyping data in the 5q22.1 region [7] .…”
Section: Introductionmentioning
confidence: 99%